The decision support system for supplementary activies on organic farms - Pažek, Karmen (Agricultura (Maribor), 2007)
In this paper we present the decision support system for ranking food processing projects on organic farms. The system is based on simulation modeling and multi criteria decision analysis. The deterministic simulation system KARSIM EKO 1.0 (DSM) consists out of deterministic production simulation models that enable different types of costs calculations for organic production and on farm food processing in the framework of supplementary activities. Simulation models results were further evaluated using a qualitative multi-attribute modeling methodology, supported by the software tool DEX-i and quantitative analytical hierarchical process - AHP, supported by Expert Choice 2000 TM software. The analysis showed that by using current model input parameter the combination of apple cider, apple vinegar and plum brandy (business alternative 1) results with the best multicriteria evaluation (EC=0,413 and DEX-i evaluation = very good).
Keywords: modeliranje procesov; simulacijski modeli; ekološko kmetijstvo; aktivnosti; agrarna ekonomika